High pressure thermal conductivity of three ethyl esters in the liquid phase. (October 2021) - Fan, Jing; Mu, Han; Gao, Chang; Song, Fenhong
Abstract: Recently, biodiesel is considered as a biodegradable, renewable and high-potential fuel which could be used directly in tradition internal combustion engines. Fuel' transport properties in high pressure are required to model the process of fuel spray, atomization and combustion accurately. This work, three ethyl esters' liquid thermal conductivity (biodiesel compounds) in the liquid phase was measured by an experiment system which is established based on a transient hot-wire method with a bare platinum hot wire. The measurements were conducted at the temperatures ranging from 292 K to 372 K and pressure up to 15 MPa. The combined expanded uncertainty of the measurement was estimated to be ±2.0% (in the 0.95 confidence level). For interpolation, the relationship between measured results with temperature and pressure were correlated as a polynomial function, and the maximum deviation of correlations were less than 0.30%.